The Stability and Anti-Angiogenic Properties of Titanium Dioxide Nanoparticles (TiO2NPs) Using Caco-2 Cells - Oladipupo Moyinoluwa David; Kim Leigh Lategan; Maria Fidalgo de Cortalezzi; Edmund John Pool (Biomolecules, 2022)
Titanium dioxide nanoparticles (TiO2NPs) are found in a wide range of products such as sunscreen, paints, toothpaste and cosmetics due to their white pigment and high refractive index. These wide-ranging applications could result in direct or indirect exposure of these NPs to humans and the environment. Accordingly, conflicting levels of toxicity has been associated with these NPs. Therefore, the risk associated with these reports and for TiO2NPs produced using varying methodologies should be measured. This study aimed to investigate the effects of various media on TiO2NP properties (hydrodynamic size and zeta potential) and the effects of TiO2NP exposure on human colorectal adenocarcinoma (Caco-2) epithelial cell viability, inflammatory and cell stress biomarkers and angiogenesis proteome profiles. The NPs increased in size over time in the various media, while zeta potentials were stable. TiO2NPs also induced cell stress biomarkers, which could be attributed to the NPs not being cytotoxic. Consequently, TiO2NP exposure had no effects on the level of inflammatory biomarkers produced by Caco-2. TiO2NPs expressed some anti-angiogenic properties when exposed to the no-observed-adverse-effect level and requires further in-depth investigation.